PENERAPAN FINANCIAL PARENTING (GEMAR MENABUNG) PADA ANAK USIA DINI - Krisdayanthi, Astrid (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2019)
In its golden age, children are very easy to absorb information. Parents have full responsibility for developing children in their golden age. The responsibility of parents is not just raising children physically, materially and emotionally, parents also need to instill life values as a provision for children's development, such as teaching about financial intelligence to children in managing their finances by saving money. Children who achieved financial freedom in the future, is the result of instilled and taught by his parents in the past. Keyword: financial parenting, financial management, childhood, save money